Effect of slow-release mineral fertilizer on the intensity of phosphorus and potassium mobilization in soil - N. A. Vasilyeva; Sh. M. Abasov; A. A. Vladimirov; Yu. A. Dukhanin; K. A. Perevertin; M. Sh. Gaplaev; I. M. Bamatov (Бюллетень Почвенного института им. В.В. Докучаева, 2024)
The search for new technologies for effective regulation of yield and soil fertility is an urgent task. The use of slow-release fertilizers can simultaneously solve both problems – reducing fertilizer rates and increasing the mobilization of soil nutrients. In this paper, the mechanism of slow-release fertilizer effect on the mobilization rate of soil nutrients was investigated using mathematical modeling on the data of field trials with winter wheat. It is shown that in the plots with the slowest dissolving fertilizer (azofoska with 20% content of polyvinyl alcohol), the highest efficiency of azofoska was achieved (an increase in yield of 1.3 t/ha and an increase in mobile forms of phosphorus in the soil of 2.5 mg/100 g soil, potassium – 8.8 mg/100 g soil and nitrate nitrogen – 4.7 mg/100 g soil). The results of phosphorus modeling quantitatively confirmed the assumption that the low rate of dissolution of fertilizer enhances the mobilization of nutrients from soil due to the absence of an excess of plant available nutrients. We provide estimates of the polymer added efficiency for a series of polymer-modified fertilizer. It is shown that this form of fertilizer can be applied to effectively reduce the amount of fertilizer required for the planned harvest, simultaneously with the possibility of bringing the soil to a higher level of effective fertility in major nutrient elements.